1999
DOI: 10.1149/1.1390863
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Codeposited Platinum/Molybdenum Oxide Electrode for Catalytic Oxidation of Methanol in Acid Solution

Abstract: An electrochemical codeposition method was used to prepare a Pt/MoO x /C composite electrode which provides a surface modification with catalytic properties for methanol oxidation in acid solution. This method allows the mixing of metal and support on a microscopic level (atomic or molecular scale), i.e., to disperse the Pt microparticles into the molybdenum oxide on a carbon (C) substrate. X-ray photoelectron spectroscopy of the composite electrode presented a broad peak in the Mo (3d) region revealing the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 19 publications
3
72
0
1
Order By: Relevance
“…Moreover, much more pronounced Mo redox process involving protons and electrons can be observed for the Mo sites located in a close contact with Pt [18,26,53,65,66]. Thus we believe that the hindered reduction of highly oxidized Mo species in the presence of strongly bound CO is a general feature of the Mo-Pt catalyst system, regardless if Mo is present in PtMo alloy form or Mo oxide is used as a constituent of the support.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, much more pronounced Mo redox process involving protons and electrons can be observed for the Mo sites located in a close contact with Pt [18,26,53,65,66]. Thus we believe that the hindered reduction of highly oxidized Mo species in the presence of strongly bound CO is a general feature of the Mo-Pt catalyst system, regardless if Mo is present in PtMo alloy form or Mo oxide is used as a constituent of the support.…”
Section: Resultsmentioning
confidence: 85%
“…In order to restore this activity, reduction of the mentioned Mo species is needed, which requires an abundant source of hydrogen in the form of hydrogen spillover [53] and/or charge transfer from Pt particles released from CO [54]. It is supposed that the hydrogen replacing the weakly adsorbed CO (evidenced by the hydrogen oxidation peak (i) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the presence of MoO 3 leads to an increase in the voltammetric peaks for hydrogen adsorption and desorption, which are presumably due to the hydrogen spillover effect within the hydrogen molybdenum bronze. This phenomenon has been attributed to the interaction between the platinum active sites and molybdenum oxides [37]. By comparing the results of PtRh/Vulcan ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Molybdenum oxide and tungsten oxide have been demonstrated to show a promoting effect on Pt-based catalysts towards the oxidation of CO, thereby mitigating CO poisoning [34][35][36] that also constitutes a limiting factor during oxidation of methanol [37][38][39]. The improvement of catalytic activities of systems containing molybdenum and tungsten oxide for CO electrooxidation was also confirmed by theoretical studies [40,41].…”
Section: Introductionmentioning
confidence: 87%
“…32 In earlier studies, undoped diamond films of perfect crystallinity were used, and the conductivity of those films was assigned to unknown structural defects caused by the temperature during film deposition. 33, 34 Gi et al 35 observed a decrease in the resistance of diamond while it was in contact with acid or in water vapor and ascribed this drop in resistance to the formation of a conducting surface film covered with hydrogen atoms. This p-type conductivity is characterized by a high carrier density.…”
Section: B832mentioning
confidence: 99%